Immune‐Related Adverse Events as Clinical Biomarkers in Patients with Metastatic Renal Cell Carcinoma Treated with Immune Checkpoint Inhibitors. (8th July 2021) - Martini, Dylan J.; Goyal, Subir; Liu, Yuan; Evans, Sean T.; Olsen, T. Anders; Case, Katherine; Magod, Benjamin L.; Brown, Jacqueline T.; Yantorni, Lauren; Russler, Greta Anne; Caulfield, Sarah; Goldman, Jamie M.; et al.
Abstract: Background: Immune checkpoint inhibitors (ICIs) are an important treatment for metastatic renal cell carcinoma (mRCC). These agents may cause immune‐related adverse events (irAEs), and the relationship between irAEs and outcomes is poorly understood. We investigated the association between irAEs and clinical outcomes in patients with mRCC treated with ICIs. Methods: We performed a retrospective study of 200 patients with mRCC treated with ICIs at Winship Cancer Institute from 2015 to 2020. Data on irAEs were collected from clinic notes and laboratory values and grades were determined using Common Terminology Criteria in Adverse Events version 5.0. The association with overall survival (OS) and progression‐free survival (PFS) was modeled by Cox proportional hazards model. Logistic regression models were used to define odds ratios (ORs) for clinical benefit (CB). Landmark analysis and extended Cox models were used to mitigate lead‐time bias by treating irAEs as a time‐varying covariate. Results: Most patients (71.0%) were male, and one‐third of patients (33.0%) experienced at least one irAE, most commonly involving the endocrine glands (13.0%), gastrointestinal tract (10.5%), or skin (10.0%). Patients who experienced irAEs had significantly longer OS (hazard ratio [HR], 0.52; p  = .013), higher chance of CB (OR, 2.10; p  = .023) and showed a trend toward longer PFS (HR, 0.71; p  = .065) in multivariate analysis. Patients who had endocrine irAEs, particularly thyroid irAEs, had significantly longer OS and PFS and higher chance of CB. In a 14‐week landmark analysis, irAEs were significantly associated with prolonged OS ( p  = .045). Patients who experienced irAEs had significantly longer median OS (44.5 vs. 18.2 months, p  = .005) and PFS (7.5 vs. 3.6 months, p  = .003) without landmark compared with patients who did not. Conclusion: We found that patients with mRCC treated with ICIs who experienced irAEs, particularly thyroid irAEs, had significantly improved clinical outcomes compared with patients who did not have irAEs. This suggests that irAEs may be effective clinical biomarkers in patients with mRCC treated with ICIs. Future prospective studies are warranted to validate these findings. Implications for Practice: This study found that early onset immune‐related adverse events (irAEs) are associated with significantly improved clinical outcomes in patients with metastatic renal cell carcinoma (mRCC) treated with immune checkpoint inhibitors (ICIs). In this site‐specific irAE analysis, endocrine irAEs, particularly thyroid irAEs, were significantly associated with improved clinical outcomes. These results have implications for practicing medical oncologists given the increasing use of ICIs for the treatment of mRCC. Importantly, these results suggest that early irAEs and thyroid irAEs at any time on treatment with ICIs may be clinical biomarkers of clinical outcomes in patients with mRCC treated with ICIs. Abstract : This study investigated the association between immune‐related adverse events and clinical outcomes in patients with metastatic renal cell carcinoma treated with immune checkpoint inhibitors.